Health Seeking Processes of Leprosy Patients in a Hill District of Nepal - Engelbrektsson, Ulla-Britt; Subedi, Madhusudan (AMC Journal, 2021)
To shorten delays in leprosy diagnosis, health-seeking processes have to be understood and documented. In 2015, the International Nepal Fellowship launched a three-year research project on the subject. One part of the project was a community study in which recent health-seeking efforts were to be studied in the light of earlier ones. The focus of this article is upon insights gained in field research in a village and its immediate surroundings in the district of Jajarkot, western Nepal. The research highlights the importance of a longitudinal, patient-focused study that covers the period from just before the start of leprosy services until late 2018. The research methods include participant observations, narratives, in-depth interviews, and documentary and statistical enquiries. The research shows that the introduction of the Multi Drug Therapy (MDT) in the early 1980s has drastically changed the local leprosy situation. The number of new cases has declined, there are far less impairments and disabilities, and those recognized as affected are no longer excommunicated. However, the delays before diagnosis tend to be long. A lack of leprosy diagnosing skills within the health services sector is one reason. The residents not recognizing early signs and symptoms is another. An expectation of leprosy endemic in certain kinship groups, and not in others, is yet another. And, for some, so is the fear of social stigma. Moreover, there is the delaying factor of more than one set of beliefs and practices in relation to leprosy:a traditional, mainly magic-religious outlook and approach which co-exists with allopathic (biomedical) views and methods.